2016
DOI: 10.3389/fpls.2016.01403
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Stem and Globally Comparison with Other Tissues in Brassica napus

Abstract: Brassica napus is one of the most important oilseed crops in the world. However, there is currently no enough stem transcriptome information and comparative transcriptome analysis of different tissues, which impedes further functional genomics research on B. napus. In this study, the stem transcriptome of B. napus was characterized by RNA-seq technology. Approximately 13.4 Gb high-quality clean reads with an average length of 100 bp were generated and used for comparative transcriptome analysis with the existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 78 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…Previous research demonstrated basic helix-loop-helix (bHLH) transcription factor family to participate in controlling cell proliferation and development of specific cell lineages [ 66 ]. Our study found bHLH TFs significant enriched during booting stage and heading time, suggesting this type of transcription factor family may play a similar role in the regulation of flower formation and heading.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated basic helix-loop-helix (bHLH) transcription factor family to participate in controlling cell proliferation and development of specific cell lineages [ 66 ]. Our study found bHLH TFs significant enriched during booting stage and heading time, suggesting this type of transcription factor family may play a similar role in the regulation of flower formation and heading.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, SA, MA and LA stage were also selected for transcriptomic analysis. The extraction of total RNA, assembly and mapping of the clean reads, and transcriptome annotation were conducted according to our previous report [ 77 ] with minor modification.…”
Section: Methodsmentioning
confidence: 99%
“…The major QTL intervals in which these related genes are located, the homologous genes in Arabidopsis, and the related GO annotations are shown ( Figure 4 and Supplementary Tables S3 , S6 ). Ko04075 is involved in the plant hormone signal transduction pathway ( Miao et al, 2016 ), which includes K14486 (auxin response factor 9), K14488 [small auxin (AUX) up RNA (SAUR) family protein], K14498 (serine/threonine-protein kinase SRK2), and K13946 (transmembrane amino acid transporter family protein). Four homologous genes were predicted in Arabidopsis and associated with the pathway.…”
Section: Resultsmentioning
confidence: 99%